2019
DOI: 10.1088/1475-7516/2019/11/022
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal gravity and gravitational-wave observations

Abstract: We discuss a modified gravity model which fits cosmological observations at a level statistically indistinguishable from ΛCDM and at the same time predicts very large deviations from General Relativity (GR) in the propagation of gravitational waves (GWs) across cosmological distances. The model is a variant of the RT nonlocal model proposed and developed by our group, with initial conditions set during inflation, and predicts a GW luminosity distance that, at the redshifts accessible to LISA or to a third-gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 59 publications
0
60
0
Order By: Relevance
“…The most interesting result is the one for Ξ 0 , which (with our rather extreme assumption of 10 yr of data taking) can be measured to an accuracy of order ∆Ξ 0 0.1, i.e. (given that our fiducial value has been taken to be the ΛCDM value Ξ 0 = 1), a relative accuracy ∆Ξ 0 /Ξ 0 10%, which is already in the ballpark of the predictions of interesting modified gravity models [38,94]. With a shorter but more realistic time of data taking, say 3-4 yr, we still expect to get ∆Ξ 0 /Ξ 0 at the level of about 20%.…”
Section: Results For the Hlvki Networkmentioning
confidence: 84%
“…The most interesting result is the one for Ξ 0 , which (with our rather extreme assumption of 10 yr of data taking) can be measured to an accuracy of order ∆Ξ 0 0.1, i.e. (given that our fiducial value has been taken to be the ΛCDM value Ξ 0 = 1), a relative accuracy ∆Ξ 0 /Ξ 0 10%, which is already in the ballpark of the predictions of interesting modified gravity models [38,94]. With a shorter but more realistic time of data taking, say 3-4 yr, we still expect to get ∆Ξ 0 /Ξ 0 at the level of about 20%.…”
Section: Results For the Hlvki Networkmentioning
confidence: 84%
“…Beside testing the accuracy to which one could confirm the validity of ΛCDM, assuming it as fiducial model, we have also tested the accuracy to which one could validate a modified gravity model. We have focused in particular on a nonlocal modification of gravity, the so-called RT model [48], for which recent work [47] has shown that Ξ 0 can reach values as large as 1.6. The model therefore gives a 60% deviation from ΛCDM in the tensor sector, despite the fact that, both in the background evolution and in scalar perturbations it is very close to ΛCDM, and indeed it fits the existing cosmological datasets at a level statistically indistinguishable from ΛCDM.…”
Section: Discussionmentioning
confidence: 99%
“…∆N = 0 (blue solid line), and for initial conditions set during inflation at ∆N efolds before the end of inflation, for ∆N = 34 (magenta, dashed), ∆N = 50 (green, dot-dashed) and ∆N = 64 (cyan, dot-dashed). From ref [47]…”
mentioning
confidence: 99%
“…The results are shown in Fig. 15 (see also [115]). These results are quite spectacular, in particular at large ∆N .…”
Section: Predictions Of the Rt Modelmentioning
confidence: 92%
“…We next compare the predictions for modified GW propagation of the RT model with the sensitivities of current and future GW detectors, elaborating on the analysis in [115,165,203,204] for ground-based detectors and in [191] Table 6. The events in a given realization of the mock catalog of joint GW-GRB detections for the HLVKI network, over 10 yr of simulated data.…”
Section: Comparison With the Sensitivity Of Current And Future Gw Detmentioning
confidence: 99%